METHODS OF DEVELOPING THE SPEECH OF PRIMARY STUDENTS BASED ON AN INTEGRATIVE APPROACH - Mamatraimova Dilshoda Chorshanbiyevna (Bright Mind Publishing, 2025)
This article describes in detail the general features of the integrative approach to speech development in primary school students. Didactic games, oratory, riddles that develop speech.
Keywords: Competence, integration, integrative approach, logical games.